Prognostic impact of pretherapeutic hemoglobin levels on all-cause mortality in cardiooncology - Hohneck, Anna; Rosenkaimer, Stephanie L.; Sieburg, Tina; Holzwarth, Jakob; Hofheinz, Ralf-Dieter; Akın, Ibrahim; Borggrefe, Martin; Gerhards, Stefan (Anticancer research, 2021)
Background/Aim: We investigated the prognostic impact of hemoglobin (Hb) levels in tumour patients receiving routine cardiological surveillance during anticancer treatment. The aim of the study was to identify independent predictors of all-cause mortality in a cardio-oncological collective. Patients and Methods: A total of 551 patients (273 males, 278 females) were enrolled in the Mannheim Registry for Cardiooncology and were included in the present analysis. Median follow-up was 41 months (95% CI=40-43). Results: Patients were grouped according to a pretherapeutic Hb-threshold (determined by ROC analysis) into cohorts with Hb<11.4 g/dl (n=232, 42.1%) and Hb >11.4 g/dl (n=319, 57.9%). Patients with lower Hb levels were older at the time of first diagnosis (63.8±14.4 vs. 59.9±15.4 years, p=0.003) and were more likely to have advanced tumour stages (92 (39.7%) vs. 83 (26.0%), p=0.0007). There were no differences regarding cardiovascular comorbidities such as hypertension or diabetes, while chronic kidney disease was more common in patients with lower Hb. Anticoagulants were used more often in patients with lower Hb (88 (37.9%) vs. 84 (26.3%), p=0.01). Left ventricular ejection fraction (LVEF) was lower in patients with Hb <11.4 g/dl (51.9±11.0% vs. 55.1±9.7%, p=0.003). Correlation analysis revealed a significant correlation of Hb levels and LVEF (R2=0.07, p<0.0001). During follow-up, a total of 140 patients (25.4%) were deceased, with significantly more deaths occurring in the group of patients with low Hb values [108 (46.6%) vs. 32 (10.0%), p<0.0001]. In multivariable analysis, Hb was identified as independent predictor for mortality (OR=5.3, CI=0.41-0.89, p<0.0001). Conclusion: Low Hb levels were identified as an independent predictor of mortality in patients with cancer. There was a significant correlation of Hb and LVEF, suggesting that low Hb values are not solely due to anaemia, but rather reflect the severity of cancer.